Exercises for special populations - Peggie Williamson (Philadelphia : Wolters Kluwer, 2019)
"This updated 2nd Edition of Williamson's highly applied Exercise for Special Populations provides just enough background for practicing and future personal trainers, exercise physiologists, and other health and fitness professionals to develop and implement exercise programs for special populations. For each condition, the book provides a general description, anatomy and physiology variances, precautions, recommendations for exercise testing and prescription, instructions and images of various exercises, and nutritional considerations. Reflecting the latest best practices in the field, the 2nd Edition features new"--Provided by publisher
Keywords: Condition physique; Persons with Disabilities rehabilitation; Exercise Therapy